Prioritising business model innovation: What needs to change in the United Kingdom energy system to grow low carbon entrepreneurship?. (February 2020) - Hall, Stephen; Mazur, Christoph; Hardy, Jeffrey; Workman, Mark; Powell, Mark
Highlights: A novel 'decision theatre' method is used to define change priorities for UK electricity utility business model innovation. Five change requirements are identified with broad support across the energy sector to enable business model innovation. There is substantial agreement in the energy industry and policy circles for these changes and from international energy investors. Without these changes to the UK sector low-carbon business models will be inhibited, slowing the energy transition. Abstract: ' What needs to change in the United Kingdom energy system, to allow low carbon business models to thrive? ' Earlier work by the authors has reported that up to £21bn of new financial value could be available to electricity utilities by 2050, in a low-carbon UK power sector. This represents up to 30% of future electricity markets. To capture new value, electricity utility business models need to evolve. This research used an elite 'decision theatre' method, in the UK, USA, and Europe, to decide on the most important changes required to the energy system to enable new [low-carbon] utility business models to thrive. The results show that there is substantial agreement on the five requirements for change, these are: (1) Clear national heat and electric transport strategies; (2) Commitment to sufficient carbon prices; (3) Simpler, principles-based regulation across the energy value chain; (4) Accessible markets for flexibility and other energy services; and (5) Managing consumers' exposure to risk. These were the changes that participants considered most important to foster low-carbon utility business model innovation. This work suggests focusing on business model innovation as opposed to technological innovation could accelerate decarbonisation, and extends the use of the Decision Theatre method in social science energy research.